Two Pearls from California - Jackson, Ian (Petits Propos Culinaires, 1993)
Readers may recall, and will do so with pleasure, the essay by Ian Jackson on ’Botanists at the Dinner Table’ in PPC 6. We recently received from him a copy of an excellent and witty review which he had written for Taxon (the quarterly journal of the International Association for Plant Taxonomy) about a book published in India which has to do with ethnobotany. This being a field of interest to many PPC readers, we asked permission to reprint the review, which was gladly given. However, the request provoked a question from the editor of Taxon: what is PPC, and should our readers know about it? Ian Jackson accordingly composed a retrospective review of PPC from issue 1 to 42. Since this is the first such appraisal of ourselves, and has the lustrous polish and sharp but amiable wit which characterize all Ian Jackson’s writing, we reprint it too, below.